Triticum aestivum L. aestivum CWI 10367 - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. aestivum Common name(s): 1, Wheat Other names: KAMTSCHATKA MESTNAJA Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 10367 Method of creation: Acquisition Date: 1988-01-01 Biological status: Traditional cultivar/landrace Other identifiers: n/a,CWI10367 MLS status: Included Historical: No